2020
DOI: 10.1037/spq0000370
|View full text |Cite
|
Sign up to set email alerts
|

Describing patterns of early literacy skill development in the first year of school and reading instruction in a New Zealand sample.

Abstract: This study describes trajectories of early literacy skill development of 99 children (n ϭ 55 boys) in their first year of primary school in New Zealand (NZ). Children were assessed twice weekly for 8 weeks on Dynamic Indicators of Basic Early Literacy Skills (DIBELS; Good & Kaminski, 2011) First Sound Fluency (FSF) and AIMSweb Letter Sound Fluency (LSF;Shinn & Shinn, 2002), with other early literacy and beginning reading skills assessed before and after progress monitoring. FSF and LSF growth trajectories were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
73
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(80 citation statements)
references
References 40 publications
7
73
0
Order By: Relevance
“…T. A. Cameron, Carroll, et al (2022) found associations between these latent classes (categories) of growth trajectories and criterion measures included after progress monitoring.…”
Section: Early Literacy Skills In the First Year Of Schoolmentioning
confidence: 88%
See 3 more Smart Citations
“…T. A. Cameron, Carroll, et al (2022) found associations between these latent classes (categories) of growth trajectories and criterion measures included after progress monitoring.…”
Section: Early Literacy Skills In the First Year Of Schoolmentioning
confidence: 88%
“…Phonemic awareness typically grows during beginning reading instruction (Castles et al, 2018). Literacy researchers have employed tools to tap developing phonemic awareness during early schooling in English-speaking contexts, assessing earlier developing onset phoneme awareness (T. A. Cameron et al, 2020; Oslund et al, 2017) to more advanced phoneme segmentation skills (Ritchey & Speece, 2006; Tindal et al, 2015).…”
Section: Early Literacy Skills In the First Year Of Schoolmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the Association of College and Research Libraries information literacy is considered a basic need in learning throughout life that is useful for all disciplines and educational levels (Elrod et al, 2012). Parents and teachers need to provide support to children to develop literacy abilities (Cameron et al, 2020;Saracho, 2021).…”
Section: Information Literacymentioning
confidence: 99%